PENILAIAN KINERJA DALAM PEMBELAJARAN KIMIA - HETTY HORTENTIE LANGKUDU (Jurnal Evaluasi Pendidikan, 2012)
This study is intended to find out the effect of performance assessment and cognitive style on the students’ achievement in chemistry by controlling the students’ prior knowledge. The research was conducted in SMA Negeri 2 and SMA Negeri Manado and the sample was 88 students in which it was chosen by using multistage random sampling technique. The research applied the experimental method by the design of treatment by level and the data were analyzed by using Analysis of Covariant (ANCOVA). The research result shows that after controlling the students’ prior knowledge: 1) the students’ learning achievement for group of students who were given the performance assessment in the form of written skill is higher than that of students who were given the performance assignment in the form of oral skill, 2) the students’ learning achievement for group of students who applied the field independent of cognitive style is higher than that of students who applied the field dependent of cognitive style, 3) there is an effect from the interaction between the performance assessment and cognitive style toward the students’ learning achievement in chemistry, 4) the students’ learning achievement for group of students who applied the field independent of cognitive style and at the same time were assessed by performance assessment in the form of written skill is higher than that of the students who were assessed by the performance assessment in the form of oral skill, and 5) the students’ learning achievement for group of students who were assessed by performance assessment in the form of written skill and at the same time they applied the field independent of cognitive style is higher than that of the students who applied the field dependent of cognitive style.